Technical and clinical performance of the thermo‐test device “Q‐Sense” to assess small fibre function: a head‐to‐head comparison with the “Thermal Sensory Analyzer” TSA in diabetic patients and healthy volunteers - Pfau, Doreen; Greffrath, Wolfgang; Schilder, Andreas; Magerl, Walter; Ohler, Carolin; Westermann, Andrea; Maier, Christoph; Doppler, Kathrin; Sommer, Claudia; Orth, Michael; Hammes, Hans-Peter; Kurz, Jochen; et al. (European journal of pain, 2019)
Background - Thermo‐test devices are rarely used outside specialized pain centres because of high acquisition costs. Recently, a new, portable device (“Q‐Sense”) was introduced, which is less expensive but has reduced cooling capacity (20°C).
Gesehen am 26.01.2021